2017
DOI: 10.17338/trainology.6.2_35
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries in single and triple hop are not detrimental to change of direction speed

Abstract: Objectives:To determine the impact of between limb asymmetries in hop performance on change of direction speed (CODS). Design and Methods: Twenty-two multisport collegiate athletes (mean ± SD; age: 21.8 ± 3.4 years, height: 178.1 ± 6.7 cm, mass:73.5 ± 7.1kg) performed three single and triple horizontal hops for distance per limb, followed by three modified 505 and 90˚cut CODS trials each side to establish imbalances between right and left, and dominant (D) and non-dominant (ND) limbs. Limb dominance was define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
115
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(134 citation statements)
references
References 32 publications
16
115
3
Order By: Relevance
“…The plant foot (direction) with the fastest completion time was defined as D COD speed performance, whereas the slower side was the ND side (5,10). Asymmetry index for D and ND COD speed performance was calculated by the formulae (dominant -non dominant / dominant x 100) (5). Asymmetry thresholds for 505 time and CODD were established using mean imbalance -(0.2 SD of the mean) (5,17).…”
Section: Asymmetry Indexmentioning
confidence: 99%
See 3 more Smart Citations
“…The plant foot (direction) with the fastest completion time was defined as D COD speed performance, whereas the slower side was the ND side (5,10). Asymmetry index for D and ND COD speed performance was calculated by the formulae (dominant -non dominant / dominant x 100) (5). Asymmetry thresholds for 505 time and CODD were established using mean imbalance -(0.2 SD of the mean) (5,17).…”
Section: Asymmetry Indexmentioning
confidence: 99%
“…Asymmetry index for D and ND COD speed performance was calculated by the formulae (dominant -non dominant / dominant x 100) (5). Asymmetry thresholds for 505 time and CODD were established using mean imbalance -(0.2 SD of the mean) (5,17).…”
Section: Asymmetry Indexmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in peak power quantified from single leg countermovement jumps (SLCMJ) or jump height from single leg drop jumps (SLDJ) have suggested that imbalances ~10% are detrimental to change of direction speed (CODS) performance (18,25). In contrast, asymmetries in jump height and distance reported from multi-planar unilateral jumps as high as 11.4% have indicated no detrimental effects on linear speed and CODS tasks (10,22); thus, it is challenging to draw sound conclusions from the available body of evidence (7). Similarly, previous research has highlighted discrepancies surrounding asymmetries and injury risk.…”
Section: Introductionmentioning
confidence: 99%